Law on arms and explosive: along with arms rules, 2016 - Malik (Delhi Law House, 2023)
Arms means article of any description designed or adapted as weapon for offence or defence and includes firearms, sharp- edged and other deadly weapons and parts of any machinery for manufacturing arms but does not include articles designed solely for domestic or agricultural uses.
Keywords: Arms (Amendment) act,2019; Arms (Amendment) act,2020; The explosives (Amendment) rules,2019